Relatório final de estágio curricular realizado no setor de assuntos regulatórios da indústria farmacêutica veterinária Ourofino Saúde Animal em Cravinhos - SP: regularização dos produtos farmacêuticos da empresa Ourofino Saúde Animal comercializados na Colômbia. - Giraldelli, Laís [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O presente relatório descreve as atividades desenvolvidas pela acadêmica de Medicina Veterinária, Laís Giraldelli, graduanda pela Faculdade de Ciências Agrárias e Veterinárias (FCAV), Unesp, Câmpus de Jaboticabal, durante a realização do estágio curricular em prática veterinária para conclusão do curso. O estágio teve como objetivo adquirir conhecimentos teóricos e práticos sobre a área de Assuntos Regulatórios em indústria farmacêutica veterinária.

This report describes the activities carried out by Veterinary Medicine student Laís Giraldelli, a graduate student at the Faculty of Agrarian and Veterinary Sciences (FCAV), Unesp, Jaboticabal Campus, during the course completion of the curricular internship in veterinary practice. The objective of the internship was to acquire theoretical and practical knowledge about the area of ​​Regulatory Affairs in the veterinary pharmaceutical industry.
Final report of the internship carried out in the department of regulatory affairs of the veterinary pharmaceutical industry Ourofino Saúde Animal in Cravinhos - SP: Regularization of pharmaceutical products from the company Ourofino Saúde Animal marketed in Colombia.
Keywords: saúde animal; medicamentos veterinários; agências reguladoras